2002
DOI: 10.1038/sj.bjc.6600619
|View full text |Cite
|
Sign up to set email alerts
|

Impact of caveolin-1 expression on prognosis of pancreatic ductal adenocarcinoma

Abstract: Caveolin-1 is a major component of caveolae and plays a regulatory role in several signalling pathways. Caveolin-1 was recently identified as a metastasis-related gene in prostate cancer. The clinical effects of caveolin-1 expression in pancreatic carcinoma, however, remain unknown. In this study, we have investigated the relationship between caveolin-1 expression and the clinicopathologic variables and clinical outcome in 79 patients with pancreatic adenocarcinoma undergoing surgical resection. Caveolin-1 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
113
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 28 publications
7
113
1
Order By: Relevance
“…Apparent from the results of our current study was the cytoplasmic localisation of the overexpressed caveolin-1 within the renal carcinoma cells. Such a subcellular location as opposed to its more traditional position at the plasma membrane appears to be a prevailing feature within different types of human cancer where caveolin-1 levels are elevated as is the case for tumours of the colon (Fine et al, 2001), pancreas (Suzuoki et al, 2002) and prostate . This suggests that, within the transformed cells, caveolin-1 is rerouted into the secretory pathway of these cells, and that such an inappropriate caveolin-1 localisation and/or accumulation may contribute to the transformed phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparent from the results of our current study was the cytoplasmic localisation of the overexpressed caveolin-1 within the renal carcinoma cells. Such a subcellular location as opposed to its more traditional position at the plasma membrane appears to be a prevailing feature within different types of human cancer where caveolin-1 levels are elevated as is the case for tumours of the colon (Fine et al, 2001), pancreas (Suzuoki et al, 2002) and prostate . This suggests that, within the transformed cells, caveolin-1 is rerouted into the secretory pathway of these cells, and that such an inappropriate caveolin-1 localisation and/or accumulation may contribute to the transformed phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in prostate cancer, increased caveolin-1 expression correlates with Gleason score, positive surgical margins, lymph node metastasis and androgen insensitivity . Additionally, caveolin-1 overexpression is related to tumour size and histopathological stage in both pancreatic ductal carcinoma (Suzuoki et al, 2002) and oesphageal squamous cell carcinoma . In all instances, elevated caveolin-1 levels were associated with tumour progression and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…21,25,26 Previously, we and others found that expression of caveolin-1 (cav-1), the major component of caveolae, is elevated in prostate cancer and other malignancies. [27][28][29][30][31][32][33][34][35][36][37][38][39][40] To address the molecular mechanism of cav-1-mediated cell survival, we explored a possible link between cav-1 overexpression and Akt activation in prostate cancer cells. When we compared PI3-K-Akt signaling activities in cav-1-expressing LNCaP cells that had undergone adenoviral vector-mediated cav-1 gene transduction with PI3-K-Akt signaling activities in cav-1-negative vector control LNCaP cells, we found that Akt, but not PI3-K activities, were significantly higher in the former.…”
Section: Mechanisms Of Akt Regulationmentioning
confidence: 99%
“…However, overexpression of CAV-1 in pancreatic carcinoma has been reported to contribute to tumor progression and has been a negative prognostic predictor following surgery (40). In addition, overexpression of CAV-1 in human pancreatic tumor cells confers resistance to ionizing radiation and CAV-1 knockdown leads to sensitivity to radiotherapy (39).…”
Section: Discussionmentioning
confidence: 99%